Application of Problem Based Learning (PBL) in a Course on Financial Accounting Principles - Nor Aziah Abdul Manaf; Zuaini Ishak; Wan Nordin Wan Hussin (UUM Press, 2011)
Purpose â€" This paper aims to share experiences in teaching a Financial Accounting Principles course using a hybrid problem based learning (PBL) method. The three specific objectives of this paper are to document how the PBL project for this course was developed and managed in class, to compare the academic performance of PBL students with non-PBL students, and to investigate the studentsâ€™ perceptions of how PBL had benefitted them.   Method â€" Based on our experience of the processes in developing and managing the PBL project, we described that process in this paper. Then, from the overall results of 1,148 students taking the Financial Accounting Principles course, we compared the academic performance between PBL and non-PBL students. In addition, we used a questionnaire to find out from the 267 students who had attended the PBL and the traditional non-PBL methods, how the various activities in the Financial Accounting Principles class had benefited them.   Findings â€" The results showed evidence of the superiority of the PBL method. The PBL students out-performed those without the benefit of a PBL experience. The survey results also indicated that a PBL approach provided significant benefits to the students in their presentation skills, teamwork, leadership and ability to use IT. In addition, student responses to the open-ended questions revealed that PBL was an acceptable way of learning accounting. PBL was a challenging way of learning, but it offered great benefits; PBL helped our students in the experimental group to improve teamwork, communication and other soft skills. However, we found PBL to be suitable only for students with some basic accounting knowledge.   Significance â€" PBL is an innovative teaching method because it uses problems in stimulating students to learn. This study has shown that PBL is a promising approach in teaching accounting. The major challenge for educators using this approach is to be able to provide well-developed problems in order to achieve the desired learning outcomes of the course.